Identifying the Determinants of Agricultural Diversification: A State wise Scenario - Biswajit Sen, P. Venkatesh, Girish K. Jha, D. R. Singh, Suresh A., Philip Kuriachen, S. S. Yeligar and S. B. Sapkal, (Indian Journal of Extension Education, 2023)
Considering the fact that agricultural production in India is highly skewed due to regional specificity and concentrating towards cereal based production with more than 50 per cent of gross cropped area under cereal crops, low degree of diversification may have long term adverse effect on sustainability and farm income. This study assesses the diversification scenario of agriculture in major seventeen Indian states and identified its key determinants alongside. It has been observed that, over the period of 1999-00 to 2013-14 these states have moderate level of agricultural diversification though it varied widely for different states with Simpson index of diversification ranging between 0.65 and 0.90. To assess the determinants of diversification, dynamic panel data (DPD) regression model was used. Analysis revealed that, previous year's cropping pattern, per capita NSDP, irrigated area, fertilizer use and terms of trade favouring high value enterprises are the major factors determining the level of diversification.